RESEARCH ON AXIAL IMPACT ENERGY ABSORPTION CHARACTERISTICS OF METAL SPHERICAL SHELL FILLED RETICULATED TUBE - ZHENG ShiWei; WU Fei; ZHANG ZhengRong (Jixie qiangdu)
In this study, the concept of energy absorption and collision avoidance of metal tubes in the transportation field is combined with a spherical reticulated shell structure with excellent vibration absorption and impact resistance in the construction field. New energy absorption structures— reticulated tubes (RT), equator skeleton spherical reticulated shells (ES), truss spherical reticulated shells (TR), and thin-walled sphere with round holes (TSH), and sphere-filled RTs-are proposed. In order to compare with the traditional energy absorption structure, aluminium alloy thin-walled tubes are also included in the study. The energy absorption characteristics were studied by drop-hammer impact test, the TSH, ES and TR-filled RTs can produce more prominent filling effect than the corresponding aluminium alloy tubes and significantly improve the carrying capacity, energy absorption, crushing forceefficiency, and specific energy absorption. Compared with the filled aluminum alloy tubes, sphere-filled RTs can not only significantly reduce the impact effect, keep the initial impact peak basically unchanged, but also significantly improve the energy absorption per unit mass. Thus, the TSH, ES, and TR-filled RTs can be new types of lightweight structures which can meet the requirements of lightweight, high energy absorption, and low impact effect.